2000
DOI: 10.1590/s0104-79302000000200005
|View full text |Cite
|
Sign up to set email alerts
|

Hematological values of some Bothrops species (Ophidia - Crotalidae) in captivity

Abstract: Blood samples of 50 healthy specimens from each of the following species: Bothrops alternatus, Bothrops jararacussu, Bothrops moojeni, and Bothrops neuwiedi diporus all kept in captivity were taken to determine the hematocrit (PCV) value, red blood cell count (RBC), total leukocyte (WBC) and differential leukocyte count, thrombocyte count, mean corpuscular volume (MCV), hemoglobin concentration (HbC), mean corpuscular hemoglobin (MCH), and mean corpuscular hemoglobin concentration (MCHC). These hematological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
16
2
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 11 publications
5
16
2
5
Order By: Relevance
“…The mean total WBC count in V. ammodytes was similar to that reported for some other snake species (Troiano et al 2000), but it was higher than those reported for pre-and posthibernating vipers held in captivity (Dutton and Taylor 2003). It is considered normal that wild populations have higher total WBC values than captive ones, probably due to elevated parasite infestations and also due to differences in ambient conditions between natural and captive environments (Salakij et al 2002;Rangel-Mendoza et al 2009).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The mean total WBC count in V. ammodytes was similar to that reported for some other snake species (Troiano et al 2000), but it was higher than those reported for pre-and posthibernating vipers held in captivity (Dutton and Taylor 2003). It is considered normal that wild populations have higher total WBC values than captive ones, probably due to elevated parasite infestations and also due to differences in ambient conditions between natural and captive environments (Salakij et al 2002;Rangel-Mendoza et al 2009).…”
Section: Discussionsupporting
confidence: 83%
“…The hematocrit (PCV) of V. ammodytes was in the range reported for other reptiles, as was the hemoglobin concentration (Dessauer 1970;Dutton and Taylor 2003). The total RBC count showed a slightly higher value than those reported for captive Bothrops species (Troiano et al 2000), but lower than those reported for captive Crotalus durissus terrificus (Troiano et al 1997), with values mostly similar to those of the king cobra (Ophiophagus hannah, Salakij et al 2002) or some lizards (Sodeinde and Ogunjobi 1994). The MCV revealed that the erythrocytes of V. ammodytes had a typical volume for a reptile, reaching an upper value reported among snakes and lizards (Frye 1991).…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The Wojtaszek method has not been used in reptiles because it requires WBC count which may also be performed by estimation rather than by direct counting and can consequently cause a high variation in the final TT result, as observed in the Amazon turtle. For this species, the estimation made with 1,000 RBC for counting TT showed high variation, contrasting with estimations made with 2,000 RBC which revealed a lower and more suitable CV, but still higher to that obtained from many reptiles (Taylor & Jacobson, 1982;Mateo et al, 1984;Wojtaszek, 1991;Troiano & Silva, 1998;Troiano et al, 1999;Troiano et al, 2000;MartinezSilvestre et al, 2004). Moreover, estimation of TT using blood smears is also subject to variability due to some factors which were already highlighted above.…”
Section: Discussionmentioning
confidence: 54%
“…In healthy reptiles, the coefficient of variation (CV) derived from WBC counts, which have been performed by several methods, may vary from 10.95 to 119.4% (Wood et al, 1984;Mateo et al, 1984;Pajés et al, 1992;Troiano & Silva, 1998;Work et al, 1998;Troiano et al, 2000;Salakij et al, 2002;Pejrilová et al, 2002;Raphael, 2003;Schumacher, 2003;Knotková et al, 2005). In Chamaeleo chamaeleon, it has been reported that NH method showed a low repeatability and a high CV due to a low concentration of leukocytes in the blood samples, which resulted in higher count errors.…”
Section: Discussionmentioning
confidence: 99%